In pursuit of 'safe' water: the burden of personal injury from water fetching in 21 low-income and middle-income countries. Issue 10 (28th October 2020) - Venkataramanan, Vidya; Geere, Jo-Anne L; Thomae, Benjamin; Stoler, Justin; Hunter, Paul R; Young, Sera L
Abstract : Introduction: Water fetching for household needs can cause injury, but documentation of the burden of harm globally has been limited. We described the frequency, characteristics and correlates of water-fetching injuries in 24 sites in 21 low-income and middle-income countries in Asia, Africa and Latin America and the Caribbean. Methods: In a survey of 6291 randomly selected households, respondents reported whether and how they had experienced water-fetching injuries. Responses were coded for injury type, mechanism, bodily location and physical context. We then identified correlates of injury using a multilevel, mixed-effects logistic regression model. Results: Thirteen per cent of respondents reported at least one water-fetching injury. Of 879 injuries, fractures and dislocations were the most commonly specified type (29.2%), and falls were the most commonly specified mechanism (76.4%). Where specified, 61.1% of injuries occurred to the lower limbs, and dangerous terrain (69.4%) was the most frequently reported context. Significant correlates included being female (aOR=1.50, 95% CI 1.15 to 1.96); rural (aOR=4.80, 95% CI 2.83 to 8.15) or periurban residence (aOR=2.75, 95% CI 1.64 to 4.60); higher household water insecurity scores (aOR=1.09, 95% CI 1.07 to 1.10) and reliance on surface water (aOR=1.97, 95% CI 1.21 to 3.22) or off-premise water sources that required queueing (aOR=1.72, 95% CI 1.19 to 2.49). Conclusion: These data suggest that water-fetching injuries are an underappreciated and largely unmeasured public health challenge. We offer guidelines for comprehensive data collection on injuries to better capture the true burden of inadequate water access. Such data can guide the design of interventions to reduce injury risk and promote equitable water access solutions.